Evaluation of Photovoltaic Energy Projects using the Real Options Valuation - Hernandez Palma, Hugo; Ibarra, Kennedy Hurtado (International Journal of Energy Economics and Policy, 2020)
The purpose of the article is to analyze from a current perspective how Real Options Valuation facilitate the evaluation of projects for the adoption of photovoltaic energy in countries such as Colombia. A mixed descriptive approach is proposed, using techniques of documentary analysis and analysis of figures. To this end, an exhaustive review of recent research on energy, project evaluation and the method of real options is carried out. As part of the results, it is highlighted that the real options method allows a greater projection of the economic/financial evaluations and also proposes lines of action thus responding to new demands of the energy markets. Due to the characteristics of the activities of the theme, real options are gaining ground in the economic/financial evaluation of projects, since until recently only traditional methods were considered for this purpose. Keywords: Renewable Energy, Photovoltaic Energy, Real Options Method, Feasibility. JEL Classifications: Q42, Q48, G17 DOI: https://doi.org/10.32479/ijeep.9974